Overexpression of the Transcriptional Regulator WOR1 Increases Susceptibility to Bile Salts and Adhesion to the Mouse Gut Mucosa in Candida albicans - Prieto, Daniel; Román, Elvira; Alonso-Monge, Rebeca; Pla, Jesús (Frontiers in Cellular and Infection Microbiology, 2017)
The transcriptional regulator Wor1 has been shown to induce the GUT transition, an environmentally triggered process that increases the fitness of C. albicans in the mouse gastrointestinal tract. We have developed strains where the expression of this gene is driven from the strong and tightly regulated tetracycline promoter. These cells retain the main characteristics reported for GUT cells albeit they show defects in the initial stages of colonization and a differential colonization along the gastrointestinal tract compared to isogenic strains, which is probably caused by their susceptibility to bile salts. We also show that WOR1 overexpressing cells have an altered metabolic activity, as revealed by a different susceptibility to inhibitors of respiration, and an enhanced adhesion to the mouse mucosa, which may contribute to their long-term favored ability to colonize the gastrointestinal tract.